The influence of Baba Nyonya acculturation on the Malacca food identity / Aisyah Tumin...[et al.] - Mohd Zahari, Mohd Salehuddin; Ishak, Noriza; Mohamad Abdullah, Khairunnisa (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Kampus Puncak Alam Campus, 2017)
Migration has been part of the process that shapes the constituent of a particular nation or place. The movement of different people from various ethnicities and cultural background into a place has enabled the process of acculturation to occur. Such process would open up the opportunity for each ethnic toadapt or adopt certain trait of culture from other ethnic and thus producing a cultural mixture that is unique. Within the scope of this study, the acculturation of Baba Nyonya from the mixture of Malay and Chinese food culture and tradition is argued has helped to shape the Malacca food identity. However, the extent to which the phenomenon is occurring is not known, as there is no particular study has been looking into this subject. Thus, this study is designed to examine the process of Baba Nyonya food acculturation and their influence on the Malacca state food identity formation.